A person affected by radiation exposure – who is he? - A. V. Akleyev; A. A. Akleyev (Радиационная гигиена)
The review dwells upon the problematic issues, uncertainties and prospects of establishing causal relationship between diseases and radiation exposure. The review discusses the challenges, uncertainties and prospects of establishing causation between exposure to radiation and diseases. The criteria that could be used to assess the radiation-induced health damage are considered. The existing practice of recognizing certain categories of citizens of the Russian Federation as people affected by radiation exposure, which is based on the establishing causal relationship between disease, invalidity, death with radiation exposure by Interdepartmental expert councils, is analyzed. Experts of Interdepartmental expert councils in taking the decision rely on to the list of diseases that should be updated consistently based on the findings of radio-epidemiological studies. To make the decision-making process objective, advanced scientific studies focused on individualization of the radiation risk and search for the biomarkers of radiation-induced effects, both deterministic and stochastic ones, are discussed.